Weight-length relationship, morphometric and meristic characters of the yellow seahorse Hippocampus kuda Bleeker, 1852 (Syngnathiformes: Syngnathidae) from central west coast of India - Pawar, H. B.; Sanaye, S. V.; Sreepada, R. A.; Ingole, B. S. (Indian Journal of Fisheries, 2019)
Eighteen morphometric and five meristic characters of the yellow seahorse, Hippocampus kuda inhabiting the coastal waters of Ratnagiri, central west coast of India, were studied. Morphometric/numerical analysis confirmed the identity of the species from Ratnagiri coastal waters as Hippocampus Kuda Bleeker, 1852. A negative allometric relationship was observed in both genders of H. kuda. The estimated weight-length relationships  (WLR) for male and female specimens, respectively were, W=0.0034 SL2.8533 and W=0.0078 SL2.5253 (r2>0.95). The biological information on morphometric and meristic characters, WLR and length-length relationship (LLR) provided in this study would be helpful for conservation and management of this vulnerable seahorse species.Keywords: Hippocampus kuda, Length-length relationship, Meristic, Morphometric, Weight-length relationship, Yellow seahorse